2015
DOI: 10.1109/tbme.2015.2444854
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional Ultrasonic Powering for Millimeter-Scale Implantable Devices

Abstract: In addition to superior energy-conversion efficiency at millimeter-scale dimensions, ultrasonic wireless powering offers deeper penetration depth and omnidirectionality as compared to the traditional inductive powering method. This makes ultrasound an attractive candidate for powering deep-seated implantable medical devices. In this paper, we investigate ultrasonic powering of millimeter-scale devices with specific emphasize on the output power levels, efficiency, range, and omnidirectionality. Piezoelectric r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 38 publications
1
68
0
Order By: Relevance
“…The electrical power from the microprobe with platinum electrodes was measured to be 164 μW (V = 3.5 V, I = 47 μA), 300 µW (V = 4.23 V, I = 71 µA), and 450 µW (V = 5 V, I = 90 µA) under mild, moderate, and strong ultrasonic intensities, respectively. These results confirmed that sufficient power can be supplied to initiate electrolysis (the wireless power transfer efficiencies were 2.7%, η = P P / output input ) 23 . The field of operation, a critical factor that determines the ablation zone and the efficacy of the treatment, was also evaluated.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The electrical power from the microprobe with platinum electrodes was measured to be 164 μW (V = 3.5 V, I = 47 μA), 300 µW (V = 4.23 V, I = 71 µA), and 450 µW (V = 5 V, I = 90 µA) under mild, moderate, and strong ultrasonic intensities, respectively. These results confirmed that sufficient power can be supplied to initiate electrolysis (the wireless power transfer efficiencies were 2.7%, η = P P / output input ) 23 . The field of operation, a critical factor that determines the ablation zone and the efficacy of the treatment, was also evaluated.…”
Section: Resultssupporting
confidence: 71%
“…The transmitting face of the PZT transducer was laid with an acoustic matching layer. The ultrasonic power utilized a continuous wave (i.e., sinusoidal wave at the resonant frequency), which allows reflection in the body and significantly reduces the angular alignment sensitivity between the transmitter and the microprobe 23 .…”
Section: Methods Fabrication Of the Microprobementioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of certain piezoelectric material is based on the consideration of the type of application, power requirement, vibration frequency, and the geometry structure. Some well-known materials used are lead zirconate titanate (PZT), aluminum nitride (AlN), barium titanate (BaTiO3), and zinc oxide (ZnO) in the form of crystal or nanowires [21] [15] [22]. Taking into account the energy requirement, the WiOptND uses ZnO nanowires complemented by thin coating of (<100 µm) of acrylic Polymethyl methacrylate).…”
Section: A Piezoelectric Nanowiresmentioning
confidence: 99%
“…The figure shows the general trend that RF is relatively low power outputs and best for near-surface implants, near-field gives high power outputs for near-surface implants, but is relatively large and ultrasound gives high power outputs even for deeply implanted small sensors. Moradi et al 2013 [80] Ahn and Ghovanloo 2016 [81] Sauer et al 2004 [82] Parramon et al 1997 [83] O'Driscoll et al 2009 [84] Kim et al 2015 [85] Tsai et al 2011 [86] Song et al 2015 [87] Charthad et…”
Section: Mechanical Energymentioning
confidence: 99%